Implementasi Pejabat Pengelola Informasi dan Dokumentasi (PPID) di Biro Komunikasi Hubungan Masyarakat Kementerian Koordinator Bidang Kemaritiman dan Investasi dalam Memberikan Pelayanan Publik - Febrianeu, Annisa; Putriana, Muria; Soegiarto, Asep (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
This research aims to understand how the implementation by the Information and Documentation Management Officer (PPID) of the Coordinating Ministry for Maritime Affairs and Investment (Kemenko Marves) enhances the quality of public services. The government plays a crucial role and bears responsibility in various state aspects, one of which is information and communication. Therefore, Government Public Relations is vital as a communication bridge between the government and the public, aiming to provide clear, transparent, and accurate information to the community. The research employs qualitative methods with purposive sampling techniques, collecting data through interviews, observations, and documentation. This study applies the data analysis techniques popularized by Miles and Huberman (1984) and relates them to Edward III's theory, which analyzes four elements: communication, resources, disposition, and bureaucratic structure in policy implementation. The validity technique used in this research is source triangulation with the subjects being three informants related to the study. The results indicate that the PPID of Kemenko Marves has successfully improved the quality of public services and enhanced the government's image.